Investigation of Galectin-3 interaction with N. meningitidis and its dimerization with laminin receptor - Alqahtani, Fulwah Yahya Saleh (2012)
Meningococcal meningitis from the causative organism Neisseria meningitidis is the leading cause of meningitis globally. This bacterium is among a limited number of pathogens that have the propensity to cross the blood brain barrier (BBB) vasculature causing meningitis. It has been recently demonstrated that Neisseria meningitidis targets the laminin receptor (37 LRP/67 LR) on the surface of human brain microvascular endothelial cells, and two meningococcal outer membrane proteins, PorA and PilQ, have been identified as bacterial ligands. Interestingly, this interaction is hypothesized to underlie meningococcal tropism for the central nervous system (CNS). There are two isoforms of laminin receptor; monomeric 37 kDa laminin receptor precursor (37 LRP) and mature 67 kDa laminin receptor (67 LR). The relationship between the 67 LR and its precursor 37 LRP is not completely understood, but previous observations have suggested that 37 LRP can undergo homo- and/or hetero- dimerization with Galectin-3 (Gal-3) to form mature 67 LR. Gal-3 is the only member of the chimera-type group of galectins, and has one C-terminal carbohydrate recognition domain (CRD) that is responsible for binding the ß-galactoside moieties of mono- or oligosaccharides on several host and bacterial molecules, including neisserial lipooligosaccharide (LOS). To identify the LOS-independent meningococcal ligands that bind Gal-3, binding of lactose liganded Gal-3 and CRD with meningococci was investigated using ELISA assay. Neisseria meningitidis bound lactose liganded Gal-3 significantly more than H. pylori, which is known to bind Gal-3 via LPS. This binding was not inhibited by increasing concentrations of lactose. Also the lactose liganded CRDof Gal-3 bound meningococci but to a lesser extent than full molecule. Importantly, binding of Gal-3 was conserved among 25 meningococcal clinical isolates tested in the current study. A meningococcal mutant lacking the glycosyltransferase required for chain elongation from the core lipid A-(KDO)2-Hep2 showed reduced binding to lactose-liganded Gal-3, but binding was not abolished indicating that the meningococcal-Gal-3 binding was not entirely LOS-dependant. Using a re-tagging approach, meningococcal PilQ and PilE proteins were identified as Gal-3 binding ligands. Mutation of the genes encoding either of these two molecules in strain MC58 led to a significant reduction in Gal-3 binding. PilQ is not known to be glycosylated, therefore its interaction with Gal-3 is likely to be protein-mediated. PilE is post-translationally glycosylated and deletion of the pilin glycosylation genes pglC and/or pglL dramatically reduced bacterial-Gal-3 binding. Given the binding of meningococcal PilQ to 37 LRP/67 LR and Gal-3, this study sought to investigate possible dimerization between 37 LRP and Gal-3 to form 67 LR. Double immunofluorescence staining of endogenous receptors revealed colocalization of 67 LR with its precursor and both of them with Gal-3 in HBMECs, astrocyte and COS7 cells. Moreover, co-expression of 37 LRP and Gal-3 fused to different fluorescent proteins indicated colocalization of these receptors in COS7 cells. Using bimolecular fluorescence complementation (BiFC) assays, the presence of 67 LR in homo- and hetero-dimer forms with Gal-3 has been confirmed in different cell lines. In addition, the recombinant laminin receptor bound Gal-3 and its CRD to comparable level. Further investigation for